318 Monopolar Versus Bipolar TURBT: Bradford Experience. (28th February 2022) - Kale, S.; Anwar, A.; Gkikas, C.
Abstract: Aim: To compare the safety and efficacy of monopolar vs bipolar TURBT. Method: This was a randomized control trial done over 18 months with patients being allotted randomly into the bipolar and monopolar arms. The study was carried out in the department of urology at BRI and YC. All consecutive patients undergoing TURBT for suspected bladder tumors were eligible for the study. The diagnosis was based on imaging and/or cystoscopy. Exclusion criteria included refusal to participate, unfitness for spinal anesthesia, and lack of tumor in the lateral wall. The primary objective was to compare the incidence of obturator jerk in monopolar and bipolar TURBT. The secondary objective was to study and compare the quality of histopathology specimen, detrusor muscle identification, and bladder perforation. Results: A total of 95 transurethral resections were done over the study period. All these patients were eligible for inclusion in the study, 50 in monopolar and 45 in the bipolar arms, were analyzed. Both the study groups were comparable for age, sex, and tumor size. The incidence of obturator jerk was greater in the bipolar arm (8.8 %% vs 2%, P- value=2.25). The difference in the incidence of obturator jerk in the two arms was not statistically significant (Chi-Square test). There was no significant difference in either of the secondary outcomes. Conclusions: The bipolar transurethral resection of the bladder tumor was not superior to monopolar resection concerning the obturator jerk, bladder perforation, and histopathological quality of the resected specimen.